Nothing happened : a history - Crane, Susan A. (Stanford University Press, 2020)
"The past is what happened. History is what we remember and write about that past, the narratives we craft to make sense and meaning out of our memories and their sources. But what does it mean to look at the past and see Nothing? This book redefines Nothing as a historical object and reorients historical consciousness in terms of an awareness of what has and has not been considered worth remembering. "Nothing" has been a catch-all term for everything that is supposedly uninteresting, not happening, all that we have skipped over or is just not there. It will take some (possibly considerable) mental adjustment before we can see Nothing in the way this author has come to think of it, with a capital N. But if we are to transform Nothing into a legitimate historical object, something that exists in the present and has existed in the past, we must see it that way. For Nothing has actually been there all along, in plain sight. When nothing has changed but we think that it should have, we might call that injustice; when nothing happened over a long, slow period of time, we might call that boring. Justice and boredom have histories. So too does being disappointed when nothing happens-for instance, when a forecast end of the world does not occur, and millennial movements have to regroup and recalibrate their predictions. By paying attention to how we understand Nothing to be happening in the present, what it means to "know Nothing" or to "do Nothing," we can begin to ask how those experiences will be remembered. Visually driven, this book explores the ways that modern photographers, artists and writers have depicted ruins, emptiness, and a lack of action. It shows us how the perception that "nothing is the way it was" has produced images and art about memories. The book also analyzes such phenomena as fake historical markers that joke about how "On This Site Nothing Happened" to reflect on our everyday awareness that important events and places from the past be remembered. Most of all, it uncovers the mistake of taking Nothing for granted--because Nothing is happening all the time"--